Used, Avoided, Restricted? Perceptions, Behavior, and Changes in Video Conferencing of German-speaking Users During and After the Pandemic - Weinberger, Lydia; Eichenmüller, Christian; Gassmann, Freya; Pugliese, Gaston; Benenson, Zinaida (Proceedings of the 2024 European Symposium on Usable Security, 2024)
The COVID-19 pandemic required a sudden deployment of video conferencing (VC) in work and social environments. A few months after contact restrictions were lifted, we conducted an exploratory online survey with 251 German-speaking participants and investigated perceptions, behavior, and changes in the use of VC apps. Particularly, we considered security, privacy, usability, and familiarity of ten popular VC apps and how these factors influenced behavior during and after the lockdown. We showed significant dependencies between the usability and security perception of ten well-known VC apps. While perceived usability was significantly correlated with familiarity in most cases, we were only able to show a connection between familiarity and security perception for some of these applications. Usability played the greatest role in deciding to use an app. Yet, depending on the app, security had a significant influence as well. A lack of usability and security also played an important role in the avoidance of apps, but the influence of third-party decisions to restrict the use was the most significant. A lack of autonomy in app usage sometimes led to the use of apps that were associated with security concerns. In some cases, uncomfortable experiences and incidents triggered by the incorrect use of functions, e.g., activating audio by mistake, led to more extensive protective measures. Participants generally perceived threats from other attendees as more realistic than from external attackers.<br
Keywords: video conferencing; UCC; UC; online meeting; privacy; security; usability; user study; survey